Health Policy Perspectives on Paediatric Tuberculosis Management: A Literature Review - Muhammad Alwy Arifin; Suci Rahmadani (Journal of Health Literacy and Qualitative Research, 2024)
Paediatric tuberculosis (TB) remains a significant public health challenge, particularly in low- and middle-income countries (LMICs). While TB is largely preventable and treatable, children often face barriers to timely diagnosis and appropriate treatment due to gaps in health policy and systems. This literature review examines health policy perspectives on Paediatric tuberculosis management, focusing on global and national policies, the integration of TB services into broader health systems, and the challenges of implementing effective Paediatric TB control programs. The review highlights successful policy interventions, the role of international guidelines, and the need for strengthened health systems to address the unique challenges of Paediatric TB.